2020
DOI: 10.1186/s12935-020-01484-5
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00261 suppresses prostate cancer tumorigenesis through upregulation of GATA6-mediated DKK3

Abstract: Background Prostate cancer is one of the leading causes of cancer death in males. Recent studies have reported aberrant expression of lncRNAs in prostate cancer. This study explores the role of LINC00261 in prostate cancer progression. Methods The differentially expressed genes, transcription factors, and lncRNAs related to prostate cancer were predicted by bioinformatics analysis. Prostate cancer tissue samples and cell lines were collected for the determination of the expression of LINC00261 by reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…For example, overexpression of FOXD2-AS1 enhanced DDPresistance in ESCC tissues and cells, and silencing FOXD2-AS1 improved DDP-resistance in ESCC (Liu H. et al, 2020). LINC00261 acts as a tumor suppressor gene in many cancers, LINC00261 suppresses the growth and metastasis of liver cancer, prostate cancer, and pancreatic cancer (Guo et al, 2020;Li Y. et al, 2020;. It has been stated in the results that LINC00261 is the candidate gene screened in our previous experiments.…”
Section: Discussionmentioning
confidence: 78%
“…For example, overexpression of FOXD2-AS1 enhanced DDPresistance in ESCC tissues and cells, and silencing FOXD2-AS1 improved DDP-resistance in ESCC (Liu H. et al, 2020). LINC00261 acts as a tumor suppressor gene in many cancers, LINC00261 suppresses the growth and metastasis of liver cancer, prostate cancer, and pancreatic cancer (Guo et al, 2020;Li Y. et al, 2020;. It has been stated in the results that LINC00261 is the candidate gene screened in our previous experiments.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, for esophageal cancer, the anti-tumor influence of LINC00261 was determined using 5-fluorouracil (5-FU) to detect increased drug sensitivity in human esophageal cancer cells [87]. Other studies have also demonstrated an inhibitory effect of LINC00261 expression in prostate cancer, choriocarcinoma, and cholangiocarcinoma [38,88,89].…”
Section: Other Cancersmentioning
confidence: 99%
“…In prostate cancer, the overexpression of LINC00261 was shown to inhibit the transcription of dickkopf-related protein 3 (DKK3) by recruiting GATA binding protein 6 (GATA6), resulting in the inhibition of tumor angiogenesis; this action was reversed by silencing DKK3. Interestingly, in prostate cancer cells, DKK3 expression induced cellular quiescence through the activation of p38 MAPK signaling pathway [ 88 ]. These findings demonstrate that LINC00261 expression may suppress prostate cancer progression, and suggest that it may be a new biomarker for early diagnosis of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations